Mobile application adjunct to the WHO basic emergency care course: a mixed methods study - Juma A Mfinanga; Hendry R Sawe; Anya L Greenberg; Andrea G Tenner; Alexandra Friedman; Paulina Nicholaus; Christian C Rose; Newton Addo; Catherine Reuben Shari; Upendo N George; Michael J Losak (BMJ Open)
Objectives The WHO developed a 5-day basic emergency care (BEC) course using the traditional lecture format. However, adult learning theory suggests that lecture-based courses alone may not promote long-term knowledge retention. We assessed whether a mobile application adjunct (BEC app) can have positive impact on knowledge acquisition and retention compared with the BEC course alone and evaluated perceptions, acceptability and barriers to adoption of such a tool.Design Mixed-methods prospective cohort study.Participants Adult healthcare workers in six health facilities in Tanzania who enrolled in the BEC course and were divided into the control arm (BEC course) or the intervention arm (BEC course plus BEC app).Main outcome measures Changes in knowledge assessment scores, self-efficacy and perceptions of BEC app.Results 92 enrolees, 46 (50%) in each arm, completed the BEC course. 71 (77%) returned for the 4-month follow-up. Mean test scores were not different between the two arms at any time period. Both arms had significantly improved test scores from enrolment (prior to distribution of materials) to day 1 of the BEC course and from day 1 of BEC course to immediately after BEC course completion. The drop-off in mean scores from immediately after BEC course completion to 4 months after course completion was not significant for either arm. No differences were observed between the two arms for any self-efficacy question at any time point. Focus groups revealed five major themes related to BEC app adoption: educational utility, clinical utility, user experience, barriers to access and barriers to use.Conclusion The BEC app was well received, but no differences in knowledge retention and self-efficacy were observed between the two arms and only a very small number of participants reported using the app. Technologic-based, linguistic-based and content-based barriers likely limited its impact.